Pengaruh Ukuran Perusahaan, Audit Tenure, dan Opini Audit Tahun Sebelumnya Terhadap Penerimaan Opini Audit Going Concern - Halim, Nanda; Annisa, Dea (Institut Bisnis dan Informatika Kesatuan, 2023)
This study aims to test whether company size, audit tenure, and previous year's audit opinion affect going concern audit opinions on mining sector companies listed on the Indonesia Stock Exchange in 2019 to 2021. The type of research conducted was quantitative research using associative method. The research sample was determined using a purposive sampling technique, so that a sample of 41 companies could be produced with a total of 123 observational data. The analytical test used is descriptive statistical analysis test, logistic regression analysis, model feasibility test, coefficient of determination test, and hypothesis testing. The results of the study prove that company size, audit tenure, and the previous year's audit opinion simultaneously influence the going concern audit opinion. Meanwhile, partially company size and audit tenure have no effect on going-concern audit opinion, while the previous year's audit opinion has an effect on going-concern audit opinion